(untitled) (XXI Century. Spanish Literature and Culture, 2004)
The most important contributions of the Spanish essay during 2007 are analyzed. The thematic variety is evident, from deep philosophical reflections to books that can be generically described as "self-help". The balance between density of thought and amenity seems achieved in the current Spanish essay. Finally, an important space is reserved for the most important philological essays.